Sentiment Analysis Against Digital Payment “GoPay”, “OVO”, “DANA”, and “ShopeePay” Using Naïve Bayes Classifier Algorithm - Lorenza Julia Ningri; Masyhuri Hamidi; Fajri Adrianto (Indonesian Journal of Economics and Management, 2023)
Financial technology is a term used by companies that offer technological innovations in the financial sector. One of the products from Fintech is digital payments. The purpose of this study is to analyze the sentiment of digital wallet services using the Twitter social media. The digital wallets taken in this study are Gopay, Ovo, Dana, and ShopeePay. This research uses the Naïve Bayes Algorithm classification method. Comment data was taken from Twitter social media which were divided into two sentiment classes, namely positive sentiment and negative sentiment. The results of this study are the most widely accepted positive sentiment among the four digital wallets is ShopeePay, the most widely received negative sentiment among the four digital wallets is Dana. Customers who have skills in using digital payments can be grouped as Well Literate in financial literacy.